Exploring the Role of ICT in developing teachers’ ICTs Competencies through Promotion-linked-training BS 17 to BS 18 QAED during PLT at the Punjab Level (Journal of Social Sciences Review, 2023)
The role of Information and, Communication Technology (ICT) in developing teacher competencies through promotion-linked training is a growing field of interest. This qualitative with case study research explores the impact of ICT on teacher training programs aimed at promoting competencies and improving teacher performance. By analyzing the use of technology in teacher training, this study seeks to understand how ICT can enhance teacher competencies and improve the overall quality of Education. Ten participants in the study were selected through a purposive sampling technique. For the data collection, face-to-face self-developed semi-structured interviews were conducted. Data were analyzed through thematic analysis. It was found that ICT has a great impact and role in developing teachers’ competencies through promotion-linked training of BS-17 to BS-18 during PLT at the Punjab level. The participants described the importance of ICT regarding their professional development. This training was described to be useful through different platforms. Resource persons used different engaging techniques like blended learning, flipped classrooms, project-based learning, and personalized learning. Microsoft applications helped them for smooth, efficient, and effective working. The results of this research provide valuable insights for policymakers, educators, and technology experts as they work to integrate ICT into teacher training programs and improve the effectiveness of teacher development initiatives.
Keywords: ICT; Competencies; Promotion- linked -Training; Continuous Professional Development; Quaid-e-Azam Academy for Educational Development (QAED); learning management system (LMS); Microsoft Office; PowerPoint; Excel